Effect of Nitrogen Fertilizer Rates and Intra-row Spacing on Yield and Yield Components of ‘Improved Huruta’ Shallot Variety (Allium cepa var.ascalonicum) at Haramaya, Eastern Ethiopia - Tsegaye Shimelis Hordofa; Kebede Woldetsadik; Wassu Mohammed (Turkish Journal of Agriculture: Food Science and Technology, 2020)
Agronomic practices for the newly released shallot variety have not been conducted in Eastern Ethiopia. To assess the effect of nitrogen fertilizer rates and intra-row spacing, a field experiment was conducted in 2017 which consisted of seven rates of nitrogen (0, 25, 50, 75,100,125 and 150 kg N ha-1) and three intra-row spacing (7.5, 10 and 12.5 cm) in factorial combination and it was laid out in a RCBD with three replications. Results of the analysis revealed that all bulb yield and yield components of the variety were highly significantly influenced by the main effects of nitrogen fertilizer and intra-row spacing. Moreover, the interaction of nitrogen fertilizer and intra-row spacing significantly influenced days to maturity, plant height, and average bulb weight and bulb dry matter. The application of 125 kg N ha-1gave high total and marketable bulb yield advantage of 32.45% (13.89 t ha-1) and 40.8% (15.47 t ha-1), respectively over the control. Plants spaced at 7.5 cm had total and marketable bulb yield advantage of 35.94% (14.54 t ha-1) and 32.83% (12.42 t ha-1), respectively over plants spaced at 12.5 cm. Therefore, intra-row spacing of 7.5 cm with the application of 125 kg N ha-1 is used for optimum yield in the study area although further research should be needed to come up with conclusive recommendation.